Education from the marxist perspective: an approach based on marx and gramsci - Amarilio Ferreira Jr; Marisa Bittar; Philip Sidney Pacheco Badiz (Faculdade de Medicina de Botucatu (Unesp), 2008)
This paper aimed to demonstrate the humanistic principles of education inherent to Marx and Gramsci's works. For both of these authors, the basis of a humanistic education are the real conditions of existence that individuals organize to keep themselves alive. Thus, individuals forge certain kinds of social relationships of production that have a double transforming function: humanizing nature and humans at the same time. In a society founded on the principle of private ownership of the means of production, this humanization process is interrupted by the alienation manifested towards objects that humans have produced. In summary, the complete human (omnilateral), educated in the arts of doing (non-alienated work) and speaking (policy of emancipation) for which the premises already lie within the sphere of capitalist society, will only historically come into being in a socialist society marked by the absence of private ownership of the means of production.